The Grandmother Language:: Writing Community Process in Jeannette Armstrong’s whispering in shadows - Haladay, Jane (Studies in Canadian Literature)

(untitled) (The University of New Brunswick, 2006)
In whispering in shadows, Jeannette Armstrong deftly employs non-standard English phraseology to convey Okanagan perceptions of the world. The author enacts a decolonizing process in her writing, exploring ways to evoke a proximate (but ultimately limited) experience of an Okanagan orality and world view in English. Penny Jackson’s sensibilities, which synthesize perceptions of sound, colour, and linguistic images as organically interrelated, are the primary manifestation of this process. The author's symbiosis of land, language, and community produces a creative well-spring, which encourages community-centered creative practices in keeping with the metaphoric implications of En’owkin, an Okanagan conception rooted in the belief that nurturing voluntary cooperation is essential for everyday living.